Using Thematic Analysis in Healthcare HCI at CHI: A Scoping Review - Bowman, Robert; Nadal, Camille; Morrissey, Kellie; Thieme, Anja; Doherty, Gavin (CHI 2023, 2023)
CHI papers researching healthcare human-computer interaction (HCI) are increasingly reporting the use of “thematic analysis” (TA). TA refers to a range of flexible and evolving approaches for qualitative data analysis. Its increased use demonstrates a change in research practices, and with that the emergence of new local standards. We need to understand and reflect upon these emerging local practices, including departures from what is advocated as quality TA practice more generally. Toward this, we conducted a scoping review of a decade of CHI publications (2012 – 2021) that researched healthcare and termed their analysis approach “thematic analysis”; 78 papers reporting a total of 100 TAs were included. We contribute a description of 1) the contexts in which TA is being used, 2) the TA approaches being conducted, and 3) how TA is being reported. Drawing on this, we discuss opportunities to improve research practice when using TA in healthcare HCI.